Distribution and kinematics of 26Al in the Galactic disc. Issue 2 (24th July 2020) - Fujimoto, Yusuke; Krumholz, Mark R; Inutsuka, Shu-ichiro
ABSTRACT: 26 Al is a short-lived radioactive isotope thought to be injected into the interstellar medium (ISM) by massive stellar winds and supernovae (SNe). However, all-sky maps of 26 Al emission show a distribution with a much larger scale height and faster rotation speed than either massive stars or the cold ISM. We investigate the origin of this discrepancy using an N -body + hydrodynamics simulation of a Milky-Way-like galaxy, self-consistently including self-gravity, star formation, stellar feedback, and 26 Al production. We find no evidence that the Milky Way's spiral structure explains the 26 Al anomaly. Stars and the 26 Al bubbles they produce form along spiral arms, but, because our simulation produces material arms that arise spontaneously rather than propagating arms forced by an external potential, star formation occurs at arm centres rather than leading edges. As a result, we find a scale height and rotation speed for 26 Al similar to that of the cold ISM. However, we also show that a synthetic 26 Al emission map produced for a possible Solar position at the edge of a large 26 Al bubble recovers many of the major qualitative features of the observed 26 Al sky. This suggests that the observed anomalous 26 Al distribution is the product of foreground emission from the 26 Al produced by a nearby, recent SN.